Answers

2014-09-13T14:20:11+08:00
Uhm well for you to answer that you need to rearrange it first remember that always put nx first after n like this 3x2+5x-2 = -7 so that you could answer it.

                                               3x2+5x-2 = -7

                                             (3x+2) (x-1)  = -7

                                3x+2 = -7        x-1 = -7
                                    -2     2         +1     1
                                 ------------          ------------
                               3x/3 = -9/3          

                                  x = -3            x = -6

                                 
0